The effect of cap and trade policy on the economy, welfare and renewable energy for the Moroccan case: a partial equilibrium approach - Mohamed Adib Ed-daoudi; Kenza Oubejja (African Scientific Journal, 2023)
In this paper, we are interested in cap-and-trade policy, or the implementation of pollution permits, as a mean to decrease CO2 emissions, which is the main cause of global warming, for the case of Morocco. To do so, we used a partial equilibrium model for the cereals market and the energy sector by simulating three scenarios of total emissions caps, namely a 1% decrease in emissions, a 5% decrease and a 7.5% decrease. We used this approach because we are concerned with one market, namely the cereals market and after designing the model wich is a system of equations capturing the interactions between fossil energy, renewable energy and cereals market, we log-linearized the model that we solved using matrix algebra with Octave. The results show that these forced emissions decreases have a very small effect on the decrease in income representing households welfare, remaining the same even in the 7.5% decrease scenario, as well as an increase in solar energy production and consumption. Therefore, a cap and trade system with a reasonnable cap will reduce emissions without affecting that much households welfare, while encouraging renewable energy production at the same time.